The Application of Independent Learning in English Learning in Vocational Schools - Cahyaning, Cindy; Anismawati, Anismawati; Aryasatya, Maheswara Handaru; Permataningtiyas , Anggie Prameswari; Shaqina , Ismi (Universitas Muhammadiyah Sidoarjo, 2024)
The Ministry of Education, Culture, Research and Technology of the Republic of Indonesia has initiated the implementation of Merdeka Belajar Curriculum to improve the quality of national education. This policy aims to introduce a new, higher quality curriculum to the younger generation, in accordance with the thoughts of Ki Hadjar Dewantara who emphasized continuous learning innovation. The concept of Merdeka Belajar gives freedom to educators and students to innovate and learn independently and creatively. According to Nadiem Makarim, Merdeka Belajar frees schools, teachers, and students to innovate and create a fun learning atmosphere. The implementation of digital teaching media such as videos and PowerPoint in English learning aims to increase student creativity and make learning more interesting and easy to understand. Teachers at SMK Muhammadiyah 1 Taman act as facilitators, getting closer to students and adjusting teaching methods to their learning styles and interests, in line with the independent curriculum. The utilization of online learning platforms such as Google Classroom and Moodle allows for structural and flexible delivery of materials and assessments. Game-based learning is implemented to improve English language skills in an interactive and fun way. Despite constraints in technology adaptation, the school actively organizes training and workshops for educators. Students' responses to the independent curriculum varied; some students felt more motivated and enjoyed the relevance of learning to real life, while others found it difficult to adapt to the independent and project-based learning methods and needed more intensive guidance.